2001
DOI: 10.1128/aem.67.1.449-452.2001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Bead Capture Eliminates PCR Inhibitors in Samples Collected from the Airborne Environment, Permitting Detection of Pneumocystis carinii DNA

Abstract: PCR detection methods are useful in studies of organisms not amenable to culture. Inhibitors in environmental samples can interfere with such assays. We describe a magnetic bead DNA capture protocol that removes inhibitors from outdoor air samples, maintaining the sensitivity of a 16S Pneumocystis carinii mitochondrial rRNA gene-based PCR.Pneumocystis carinii pneumonia (PCP) remains the most common opportunistic infection among individuals diagnosed with AIDS in the United States (5). However, basic knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 25 publications
(11 reference statements)
0
37
0
Order By: Relevance
“…Studies applying filtration for bioaerosol collection have used sampling times ranging from a few minutes to several hours (27,54), or even as long as 24 h (55,56). It has been shown that prolonged sampling periods by impaction-based samplers increase the risk of microorganism viability loss (16,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Studies applying filtration for bioaerosol collection have used sampling times ranging from a few minutes to several hours (27,54), or even as long as 24 h (55,56). It has been shown that prolonged sampling periods by impaction-based samplers increase the risk of microorganism viability loss (16,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for pathogenic agents with low infectious dose units (e.g., Neisseria meningitidis and Mycobacterium tuberculosis with infectious doses of <10 organisms) it is important to know the number of CO especially for some pathogens, e.g., V. cholerae, where the major contributors to infection are the culturable cells as opposed to active but not culturable organisms, ABNC (Nelson et al 2008). An instrumental technique, quantitative polymerase chain reaction detection (PCR), has the potential to account for the ABNC as well as species that are more difficult to culture, so quantitative PCR is considered to be more comprehensive than culture analysis (Maher et al 2001). …”
Section: Sampling Systemmentioning
confidence: 99%
“…Wilson (1997) provides an extensive list of sample substrates and associated inhibitors. Trace amounts of humic substances, heavy metals, constituents of bacterial cells, proteolytic enzymes, and high concentrations of non-target DNA have all been associated with the inhibition of the PCR in environmental matrices such as air, soil, water, sewage, and sediment (Alvarez et al, 1994(Alvarez et al, , 1995Keswani, Kashon, & Chen, 2005;Maher, Dillon, Vermund, & Unnasch, 2001;Roe et al, 2001;Wilson, 1997).…”
Section: Introductionmentioning
confidence: 97%